1998
DOI: 10.1017/s0954394500001332
|View full text |Cite
|
Sign up to set email alerts
|

Aspects of Spanish deictic expressions in Barcelona: A quantitative examination

Abstract: This sociolinguistic investigation analyzes an innovative usage of Spanish motion verbs, demonstratives, and locatives in Barcelona that involves crosslinguistic pragmatic transfer. Speakers in the two social networks examined (N = 58) use these Spanish deictics following pragmatic rules that generally correspond to the rules for their Catalan counterparts. Quantitative analysis demonstrates that this innovative usage of the Spanish deictics is not predictable from the lexical form of the deictic systems in bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…The first of these three categories presented venir with a null subject, as in (15), the second presented venir in VS word order due to its status as an unaccusative verb (Burzio, 1986 ), as in (16), and the third presented venir in SV word order which was expected to be the least acceptable of the three, as in (17), since this word order is non-canonical with an unaccusative verb. These three categories were based on the productions of the bilingual children vis à vis the literature on the constraints on venir in Spanish (Gathercole, 1978 ; Vann, 1998 ; Lewandowski, 2007 ). Thus, their acceptance could be revealing of patterns not attested in the previous literature.…”
Section: Acceptability Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…The first of these three categories presented venir with a null subject, as in (15), the second presented venir in VS word order due to its status as an unaccusative verb (Burzio, 1986 ), as in (16), and the third presented venir in SV word order which was expected to be the least acceptable of the three, as in (17), since this word order is non-canonical with an unaccusative verb. These three categories were based on the productions of the bilingual children vis à vis the literature on the constraints on venir in Spanish (Gathercole, 1978 ; Vann, 1998 ; Lewandowski, 2007 ). Thus, their acceptance could be revealing of patterns not attested in the previous literature.…”
Section: Acceptability Experimentsmentioning
confidence: 99%
“…In Catalan, venir allows for the speaker or the addressee to be the reference, while European Spanish carries a stricter requirement that it can only be the speaker. Vann (1998) has shown in an elicited production task that for adult bilingual speakers in Barcelona, there is transfer of the Catalan patterns into Spanish. Likewise, judgment data reported in Chui (2016) shows that while adult native speakers of Spanish require the path of motion to be directed toward the speaker, heritage Spanish speakers (native speakers of both English and Spanish) allow for the hearer to fill this role, ostensibly indicating that these bilinguals may have more flexible parameters in Spanish 1 .…”
Section: Introductionmentioning
confidence: 99%
“…Previous works on deictic verbs in Spanish (Gathercole, 1978;Lewandowski, 2007;Vann, 1998;Verde, 2014) have examined the verbs venir, traer, ir, and llevar through the framework established for English come, bring, go, and take by Fillmore in his Santa Cruz Lectures on Deixis (1971). Gathercole (1978, pp.…”
Section: Introductionmentioning
confidence: 99%
“…These studies have generally regarded the verbal-deictic preferences of Spanish as categorically different from English with regards to the ability of the speaker to utilize the come or bring verbs to describe motion towards the hearer ("I'm coming over right now"). Nonetheless, Vann's (1998) work on the Spanish spoken by bilingual speakers of Catalan and Spanish shows that the deictic system of one language is not always impervious to the influence of competing deictic systems from another language. He found that bilingual speakers of Catalan and Spanish showed novel usages of Spanish motion verbs due to "crosslinguistic pragmatic transfer" (Vann, 1998;263).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation